Associação entre qualidade de vida, perfil socioeconômico e a disponibilidade a pagar por procedimentos odontológicos de urgência - Bezerra, José Iury Braga (2024)
Willingness to pay (WTP) is one of the methods used to evaluate the valuation of health, referring to the process of assigning economic and/or social value to health-related aspects. This process may involve analyzing the economic impact of health interventions and the value attributed to people's well-being and health. Quality of life is directly related to oral health conditions, as dental problems can significantly affect an individual's physical and psychological well-being. In this context, this dissertation aims to analyze the relationship between oral health-related quality of life and willingness to pay (WTP) for dental procedures. This is an observational, cross-sectional, descriptive, and analytical study, including individuals over 18 years old, of both sexes, and with no geographical restrictions in Brazil. Data collection was conducted through digital forms on the Google Workspace platform (Google Forms), containing questions about socioeconomic profile, quality of life, and willingness to pay for dental procedures. The sample consisted of individuals aged between 18 and 79 years, mostly female (67.7%), with a family income of 1 to 2 minimum wages (26.1%), higher education (complete or incomplete) or postgraduate education (87.4%), and no professional connection to dentistry (79.6%). Initially, a descriptive analysis of the data was performed, obtaining absolute frequencies of variables, the median, and the interquartile range (25th and 75th percentiles). A multivariate linear regression was then applied to evaluate the strength of the association between the variables. The dependent variables were WTP for emergency treatment (pain relief) with endodontic therapy and WTP for emergency treatment (pain relief) with tooth extraction. The independent variables were oral health-related quality of life, measured by the Oral Health Impact Profile (OHIP), family income, education level, and respondent profile, with sex included as an adjustment variable in the multivariate model. In the initial model, variables with p < 0.20 in the bivariate analysis were included. The OHIP showed an impact in the bivariate analysis (p=0.002) but lost significance in the adjusted model. On average, individuals with incomes above 10 minimum wages were willing to pay R$ 370.83 more for emergency treatment (pain relief) with endodontics and R$ 87.11 more for emergency treatment (pain relief) with tooth extraction. The respondent's professional profile was also significant: dental professionals showed a higher willingness to pay compared to the general population (p<0.001). The analysis revealed that OHIP did not influence WTP for emergency treatments involving endodontics or tooth extractions. It was concluded that, in the studied context, oral health-related quality of life did not affect the willingness to pay (WTP) for emergency dental treatments such as endodontics and tooth extractions. Other factors, such as income, education level, and the respondent's professional relationship with dentistry, played a more relevant role in determining WTP.